Zygomatic implants placed in atrophic maxilla: an overview of current systematic reviews and meta-analysis - Shaqayeq Ramezanzade; Julian Yates; Frank J. Tuminelli; Seied Omid Keyhan; Parisa Yousefi; Jose Lopez-Lopez (SpringerOpen, 2021)
Abstract Background Zygomatic implants are a treatment option for severely atrophic maxilla. Main text This study aimed to summarize and evaluate systematic reviews assessing the clinical outcomes of zygomatic implants including survival/failure rate and complications. PubMed-MEDLINE, Google Scholar, LILACS, and the Cochrane Database were searched up to April 2020. Risk of bias assessment was conducted by the AMSTAR tool. Initial searches yielded 175 studies. These were assessed, and following title abstract and full-text evaluation, 7 studies (2 meta-analyses) were included in the final review. According to the AMSTAR tool, 1 was deemed high quality, 4 were classified as medium, and 2 as low quality. The mean AMSTAR score (±SD) was 5.28 of 9 (±2.36) ranging from 2/9 to 9/9. The reported survival rates ranged from 95.2 to 100% except for resected maxillas, which established higher failure rates up to 21.43%. Concerning the complications with the zygomatic implants, various surgical and prosthetic complications were reported with sinusitis being the most frequently observed complication. Zygomatic implants appears to offer a promising alternative to formal bone grafting techniques with lower costs, less complications, less morbidity, shorter treatment times, and comparably high survival rates. Conclusion Complications were rare and usually easy to manage. However, the treatment should be directed by appropriately trained clinicians with noticeable surgical experience.